2022
DOI: 10.2147/cmar.s316700
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Tumor Microenvironment in Triple Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a special subtype of breast cancer, accounting for 10-20% of breast cancers with high intrinsic heterogeneity. Its unique immune microenvironment, including high expression of vascular endothelial growth factors, tumor infiltrating lymphocytes (TILs), tumor-associated macrophages (TAMs), and other molecules that promote the growth and migration of tumor cells, has been shown to play a dual role in the occurrence, growth, and metastasis of TNBC. Understanding the TNBC mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 163 publications
(262 reference statements)
1
52
0
Order By: Relevance
“…The fact that the tumor microenvironment (TME) components and functions differ across the various subtypes of breast cancer is well-established [83]. Since the abundance of TAMs varies in different subtypes of breast cancer, the risk scores of these cases also varied accordingly (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the tumor microenvironment (TME) components and functions differ across the various subtypes of breast cancer is well-established [83]. Since the abundance of TAMs varies in different subtypes of breast cancer, the risk scores of these cases also varied accordingly (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the 3-gene TNBC score is related to TIL infiltration, where a lower score was associated with a high infiltration of TILs. This observation might be explained by the influence of CCL5 [ 36 , 37 ]. The expression of this gene causes a lowering of the score and, biologically, participates in the recruitment of TILs in TNBC [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNBC has an immunogenic microenvironment that contains a variety of cell types, including tumour-infiltrating lymphocytes (TILs), tumour-associated macrophages (TAM), neutrophils and fibroblasts, and NK cells [ 23 ]. It has been found that tumours with high levels of TILs—including CD20+ B cells, CD4 and CD8+ T cells, and CD138+ plasma cells—have better pathological Complete Response (pCR), Disease-Free-Survival (DFS) and OS rates.…”
Section: Targeting Microenvironment (Angiogenesis and Immune System)mentioning
confidence: 99%